TERMS OF NAVIGATION ON THE LOWER PART OF RIVER VAH (Perner's Contacts, 2014)
The article is about the analysis of the status quo of waterway transport on the lower part of the Vah River. In the article you can also find the economic comparison of combined and waterway transport between Šala and Regensburg. There are also elaborated designs for the improvement of water transport on the lower Vah from the points of view of technical and technological.
Keywords: water transport; lower Vah; pushing barge